The effect of rest interval length on the sustainability of squat and bench press repetitions - Willardson, J. M.; Burkett, L. N. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to compare the effect of 3 different rest intervals on the sustainability of squat and bench press repetitions over 5 consecutive sets performed with a 15 repetition maximum (RM)-load. Fifteen college-age men with previous resistance training experience were tested weekly over a period of 3 weeks. During each testing session, 5 consecutive sets of the squat and the bench press were performed with a 30-second, 1-minute, or 2-minute rest interval between sets. For each exercise, significant declines in repetitions occurred between the first and the fifth sets (p = 0.000). For the squat, a significant difference in the ability to sustain repetitions occurred between the 30-second and 2-minute rest condition (p = 0.003). However, differences were not significant between the 30-second and 1-minute rest conditions (p = 0.986) and between the 1-minute and 2-minute rest conditions (p = 0.042). For the bench press, significant differences in the ability to sustain repetitions occurred between the 30-second and 2-minute rest conditions (p = 0.000) and between the 1-minute and 2-minute rest conditions (p = 0.000). However, differences were not significant between the 30-second and 1-minute rest conditions (p = 0.019). For each exercise, the number of repetitions completed on the first set was not sustained over subsequent sets, irrespective of the rest condition. These results suggest that when short rest intervals are used to develop muscular endurance, the intensity should be lowered over subsequent sets to sustain repetitions within the range conducive to this training goal.